Backward Vertical Integration Strategies and Competitiveness of Firms in EPZ Kenya - Njuguna, Naomi; Kwasira, Josphat; Kariuki, Anne (International Journal of Strategic Management, 2024)
Purpose: The main purpose of the study was to determine the influence of backward vertical integration strategies on the competitiveness of firms in the Export Processing Zones (EPZ), Kenya. Methodology: Both quantitative and qualitative approaches were used in this study, meaning that both descriptive statistics and inferential statistics were employed. Descriptive technique, specifically survey was used in the research design. The target population was all the 137 EPZ firms within Kenya and the sample was drawn from this population. The stratified random sampling technique was used. The EPZ firms are situated within the 74 gazetted zones, out of which 69 are privately owned and operated while 5 are public zones. The quantitative data that was collected was analyzed using the Statistical Package for Social Scientists. Further, the significance level of each independent variable was tested against the dependent variable at 95% level of confidence using ANOVA, regression and correlation techniques. Findings: The findings showed that backward vertical integration strategies had a positive and significant influence on the competitiveness of firms in EPZ, Kenya, at 0.151, p<0.05 and 0.432, p<0.05 when the moderating variable firm size is included. Unique Contribution to Theory, Practice and Policy: This study contributes to both the resource-based view and the theory of dynamic capabilities. It lays emphasis on the importance of resources in attaining competitiveness as suggested in these theories. Besides, the study emphasizes the need for firms to have policies aimed at ensuring raw materials supply stability, lower transaction costs and enhanced economies of scale. The findings of this study are significant because the Government of Kenya envisages that the EPZ program is expected to play a critical role in the manufacturing sector contributing 20% to Gross Domestic Product (GDP) by 2030. This will subsequently lead to an increase in employment opportunities, real-value added growth, and foreign direct investment (KNBS, 2022). The study recommends a review by the EPZ Authority in Kenya , of the underlying aim of using backward vertical integration strategies as means of gaining competitive advantage competitiveness and the inclusion of this strategy in the various EPZ firm's policies and procedures.